Production and characterization of powder from drone brood of honeybees (Apis mellifera) - Goncalves, J. C. (2025)
Drone bee brood are a natural source of food with potential for human nutrition. This work aims to investigate the production and extraction of the drone bee brood (larvae and pupae), as well as the production of powder from this insect for food applications. To produce the drone brood (DB), in some hives of the colony appropriate empty frames were placed. Some measurements were done in the hive to monitor the global wellbeing of the colony, namely, temperature, relative humidity, and weight. After approximately one month, the frames were removed from the hives and frozen. The yield of DB by frame was 38%. For the extraction of the drone brood, different methods were tested, being the best ones the cold room extraction (∼ 6.5 °C), on a cold surface extraction (∼ 11 °C), and in boiling water extraction (100 °C). The results show that the extraction efficiencies were 74.3% (336.3 s), 62.5% (246.8 s) and 84.9% (332.0 s), for extraction in a cold room, on a cold surface, and in boiling water, respectively. After extraction, two drying processes were tested: evaporation and freeze-drying, being the last one the recommended, preserving in a better way the appearance and composition of the DB. DB powders presented different colour characteristics according to the extraction method used. The powder obtained by boiling extraction was darker than the one produced with cold extraction. Powders are rich in protein, fat and carbohydrates, being the fat content quite high for DB powders produced by boiling extraction method.